Effect of temperature and relative humidity on the rate of infestation of bitter gourd by the fruit fly, Bactrocera cucurbitae (Coquillett) (Diptera : Tephritidae) - Sikdar, B; Shafiullah, M; Zaman, Rashed; Kabir, MF; Uddin, MA (University Journal of Zoology, Rajshahi University, 2007)
Key words: Temperature; relative humidity; infestation; bitter gourd; fruit fly Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 99-103